PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI PADA RUMAH SAKIT UMUM DAERAH DR. ABDUL RIVAI KABUPATEN BERAU - Endah, Ari (ECO-BUILD, 2018)
The purpose of this study is to know clearly about the effect of supervision on the discipline of employee staff RSUD Dr. Abdul Rivai District of Berau. This writing uses analysis tools that are Product Moment correlation coefficient, simple linear regression equation and hypothesis testing with Test r. Based on the results of the research can be seen that the simple linear regression equation about the influence of supervision on the discipline of employee staff RSUD Dr. Abdul Rivai Berau is Y = 26,94 + 0,61 X. The value of product moment correlation coefficient is 0,5287, so r> 0 (0,5287> 0) hence there is positive linear correlation between supervisory variable and discipline variable work. In this case the closeness of the relationship between the two variables can be interpreted as a fairly good correlation (on a scale of 0.400 to 1.599). The value of t arithmetic is 3.30 while the r value of the table is 0.361. So that th value greater than rt (3,30> 0,361), hence hypothesis proposed in this research accepted or proved that supervision have an effect on signifikan to work discipline employee of RSUD Dr. Abdul Rivai District of Berau